Utilization of glial fibrillary acidic protein and galectin-3 in the diagnosis of cerebral infarction patients with normal cranial tomography - Ekingen, E.; Yilmaz, M.; Yildiz, M.; Atescelik, M.; Goktekin, M. C.; Gurger, M.; Ilhan, N. (Wolters Kluwer Medknow Publications, 2017)
Objective: It was aimed to determine whether levels of glial fibrillary acidic protein (GFAP) and Galectin-3 contribute to the diagnosis of cerebral infarction in clinically suspected ischemic stroke patients with normal computerized cranial tomography (CCT) in the emergency department. Materials and Methods: In this study, patients above the age of 18 years who presented to emergency department of Firat University between December 2011-November 2012 and were diagnosed with cerebral infarction were included. Exclusion criteria were as follows: symptom onset exceeding 24 hours, trauma, pregnancy, acute myocardial infarction, acute pulmonary embolism, chronic renal insufficiency and steroid therapy. Results: A total of 90 participants, forty patients with ischemic infarction who were diagnosed by CCT and clinical findings (Normal CCT in 17 patients and CCT with an area of infarction in 23 patients) and fifty healthy controls, were included in this study. Compared with the control group, levels of Galectin-3 and GFAP were found to be significantly increased in patients with ischemic infarction (P <0.001 and P = 0.01, respectively). It was found that levels of Galectin-3 and GFAP were significantly increased in ischemic stroke patients with normal CCT compared to the control group (P = 0.04 and P = 0.025, respectively). In ROC curve analysis, we detected %70.59 sensitivity and 70% specificity (AUC = 0.684, P = 0.0213, 95% CI: 0,558-0.792) with a cutoff value of 33.24 ng/ml for GFAP and 76.47% sensitivity and 68% specificity (AUC = 0.734, P = 0.0048, 95% CI: 0.611-0.834) with a cutoff value of 0.84 ng/ml for Galectin-3. No correlation was found between National Institutes of Health Stroke Scale (NIHSS) scores and Galectin-3 and GFAP (r = 0.251, P = 0.118 and r = 0.164, P = 0.311, respectively). Conclusion: The levels of Galectin-3 and GFAP were increased in acute ischemic stroke patients.
Keywords: Galectin-3; glial fibrillary acidic protein; ischemic stroke